Diet Habits, Hydration Practices, Perceived Fatigue, and Motivation in Adolescent Swimmers - LABAR Riad (Sport system journal, 2026)
The purpose of this study is to examine diet habits, training hydration practices, perceived fatigue, and motivation in 109 adolescent competitive swimmers. Analyses used Chi-square tests and Spearman correlations to assess associations among nutrition knowledge, sweets intake, fast-food/industrial meals intake, hydration during training, fatigue and motivation. Low training hydration was strongly associated with high fatigue (χ²=21.36, p ˂0.001) and hydration frequency was very strongly inversely correlated with fatigue severity (rs=−0.829, p ˂0.001). Higher nutrition knowledge was associated with better training hydration (χ²=4.40, p ˂0.05) and correlated with lower fatigue (rs=−0.275, p ˂0.01). A diet-habits and hydration summary score (SQA) was associated with high fatigue (χ²=12.75, p ˂0.01) and low motivation (χ² =8.28, p ˂0.05), and correlated with both fatigue (rs=−0.527, p ˂0.001) and motivation (rs=0.396, p ˂0.001). These findings highlight training hydration routines and overall behavior patterns as practical targets for youth swimming programs. In adolescent swimmers, training hydration and overall diet quality were consistently associated with perceived fatigue and motivation, supporting the value of simple diet-quality indices.
Keywords: Adolescent Swimmers; Diet habits; Hydration; Fatigue; Motivation